An Islamic Intellectual Heritage in China Introducing Jin Tianzhu (1690-1756) and his Qing Zhenshiyi - Zhanming, Ma (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
This paper contains a brief accounts of the life and works of an eighteenth-century Chinese Muslim scholar by the name of Jin Tianzhu (1690-1756). Special discussion is devoted to the author’s work known as Qing Zhenshiyi which means “Clarifying misunderstandings about Islam”. Completed in 1738 the book attempts to explain to both Muslim and non-Muslims in China the core teachings and practices of Islam by comparing them to the teachings of the other religions in China. The significance of the book lies in the fact that it was written at the time when Islam was widely misunderstood and Muslims became the hate target of some government officials. The author of this paper is about to complete his doctoral dissertation on this book, comprising of an edition and translation into English of the classical text as well as commentary on it. The study would help to throw much light on the intellectual concern of Muslims in eighteenth century in China.